Assessing the completeness and correctness of the registration of malignant mesothelioma in Belgium. (August 2018) - Rosskamp, Michael; De Schutter, Harlinde; Henau, Kris; Nackaerts, Kristiaan; Van Meerbeeck, Jan P.; Praet, Marleen; Van Eycken, Liesbet
Highlights: Comparing population-based registries resulted in 95% of concordant cases. Completeness and correctness of mesothelioma registration was enhanced. Reasons for misclassification and under-registration were elucidated. Distinct immunohistochemical patterns were observed by mesothelioma histology. Long-term survivors had distinct clinical and biological characteristics. Abstract: Objectives: Malignant mesothelioma (MM) is a rare and aggressive cancer mostly caused by asbestos exposure, and for which the diagnosis is difficult. This study aimed to assess the completeness and correctness of MM registration using 3 independent national databases: the Belgian Cancer Registry (BCR), the population-based mortality statistics (certificates of death, COD), and the Belgian Mesothelioma Registry (BMR). Methods: The study cohort included all MM reported to the BCR and diagnosed between 2004 and 2012 (n = 2292), all patients reviewed by the pathology commission of the BMR (2004–2012; n = 2019), and COD data for all Belgian citizens (2004–2013). Available data were compared in terms of registered cases, histological diagnosis, performed immunohistochemical (IHC) tests, and IHC test results. Results: Comparison of BCR with BMR registrations showed 94.8% concordant cases. The proportion of MM diagnoses originally reported to BCR with unspecified MM morphology was reduced from 25.8% to less than 1%. Results: from IHC tests were available for 95.3% of concordant MM cases. Different IHC patterns could be distinguished by MM histology. MM cases registered at BCR for which COD mentioned an MM as underlying cause of death represented 76.4% of deceased cases. MM long-term survivors (survival >3 years; 10.9%) were characterised by distinct clinical and biological characteristics. Conclusions: A comparison of independent Belgian MM registration databases elucidated under-registration and misclassification and revealed possible reasons for observed discordances. Combining all the available information resulted in enhanced completeness and correctness of MM registration in Belgium and allowed for the identification and characterisation of MM long-term survivors.